Arab nevek a rendvédelmi adatbázisokban – rendszerezés, értelmezés, átírás (Academic Journal of Internal Affairs, 2019)
The continuously growing presence of Arabic culture in Europe raises new challenges for Hungary. Diverse variety of law enforcement’s expertise are contained by these challenges. In order to find a proper solution to these challenges of immigration, it is necessity for the law enforcement agencies to get familiar with the Arabic culture and their way of thinking, understand the structure of Arabic names; moreover, we have to get to know the problematic situation of the transcription of Arabic names. All these are essential for the highest level of efficiency at law enforcement agencies.
Keywords: arabic names; identify; database; migration